Analisis Alih Fungsi Lahan Menggunakan Regresi Logistik Ordinal (Jurnal Geomine, 2021)
The occurrence of landslides can not be separated from conditions that are prone to landslide movements such as steep slopes and high rainfall. The occurrence of landslides is also exacerbated by the indiscipline of the community in using land according to its function, which is called land conversion which can be a trigger factor for landslides. Conducting research on land use change is important to see the impact caused by human activities. The purpose of this study was to analyze the effect of land conversion on landslide hazard levels in Samigaluh District, Kulon Progo Regency. The method in this research was descriptive quantitative using primary data, namely field surveys and secondary data collection. The steps on this research were conducting field observations about the occurrence of land conversion and then retrieving level of landslide hazard at the observation point of land use change. Data analysis was performed using ordinal logistic regression. The result of the analysis showed that the p value (0.036)